ESTIMATING THE PERFORMANCE OF THE GAKKUMDU IN HANDLING REPORTS AND FINDINGS OF VIOLATIONS OF THE 2024 ELECTIONS - Nurhayati, Dwi Astuti Wahyu (JURNAL TRIAS POLITIKA, 2024)
: It is imperative that vulnerabilities in the 2024 election law enforcement system be identified in order to provide learning and development for election organisers and other law enforcement organisations. This study aims to comprehend the kinds of cases that remain unresolved, the actions that are taken, the opinions of GAKKUMDU, about the receipt of reports and violations, the challenges encountered in managing and resolving issues, and the perspectives that the public will have going forward regarding election dispute resolution. Using a juridical-normative approach, the research uses normative legal research methodologies to analyse the relevant legal norms in the context of addressing election-related criminal offences in 2024.The results show two different types of reports: one was registered and included the village heads' lack of neutrality, while the other four were not (distribution of staple food packages, damage to campaign media (APK and APS), lack of transparency by the Election Supervisory Body, and circulation of the "Tabloid Indonesia Maju". Several steps were taken by GAKKUMDU in handling reports and violations included harmonising perceptions is the result of the actions conducted, which include beginning harmonisation, receiving reports, managing violations, monitoring, and evaluation. Assessing the Gakkumdu Center's efficiency in addressing electoral infractions in 2024 and aligning perceptions entails coordinating the opinions, strategies, and tactics of the several stakeholders engaged in election law enforcement are obligation to conduct. It is intended that by comprehending the current problems, practical measures to strengthen accountability, better the election law enforcement process, and guarantee a more equitable and transparent election can be found. The collaboration is not only done by Bawaslu, the Police, or the Prosecutor's Office but also in order to manage the election offences of 2024.